MAGA FORCES UNDER SCRUTINY: EXAMINING REPRESENTATION IN PRESIDENT BIDEN’S SPEECH - Lie, Janice; Tanto, Trisnowati (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2024)
In the context of rising political polarization in the United States, President Joe Biden's 2022 speech, delivered ahead of the midterm elections, sought to address the growing ideological divide and the perceived threat posed by the MAGA (Make America Great Again) forces. This research critically examines President Joe Biden’s 2022 speech, delivered in the context of the U.S. midterm elections, focusing on the portrayal of the MAGA (Make America Great Again) forces as a threat to U.S. democracy and the Constitution. Using Van Dijk’s Critical Discourse Analysis (CDA) framework and Stuart Hall’s representation theory, the study analyzes the speech through macrostructure, microstructure, and superstructure to uncover how Biden constructs the MAGA forces as a negative representation in contrast to the Democratic Party’s commitment to equality and democracy. The research employs a qualitative method, examining linguistic tools such as examples, repetition, contrast, and comparison to understand how Biden uses language to highlight the disruptive and violent actions of the MAGA forces. Through examples like the January 6th Capitol riot and election denialism, Biden portrays the MAGA forces as violent, authoritarian, and opposed to democratic processes. Repetition of key phrases, like “no right,” emphasizes the regressive nature of the MAGA agenda, while contrast and comparison serve to define the Democratic Party’s vision of unity and democracy against the MAGA forces’ divisive actions. The superstructure of the speech, organized into distinct arguments and sub-arguments, further reinforces the portrayal of the MAGA forces as a serious threat to the nation’s values, calling for collective action to preserve democracy. The findings suggest that Biden’s strategic use of discourse positions the MAGA forces as an adversarial force, aiming to strip away fundamental rights and disrupt the democratic order. This research contributes to the broader field of Critical Discourse Analysis by exploring the role of political rhetoric in shaping public perceptions of political movements. It underscores the importance of critically engaging with political speeches to reveal implicit messages and power dynamics within discourse. The study’s implications point to the need for ongoing discourse analysis to better understand the complex interplay between language and political ideology, particularly in the context of contemporary political polarization. Future research could extend this analysis by examining additional speeches or exploring the broader impact of discourse on public opinion and political behaviour.